Signatures of mRNA Alternative Polyadenylation in Arabidopsis Leaf Development - Yu, Zhibo; Hong, Liwei; Li, Qingshun Q. (Frontiers in Genetics, 2022)
Alternative polyadenylation (APA) of pre-mRNA is an important post-transcriptional mechanism that modulates gene expression, leading to transcriptome and function diversities. The role of APA in Arabidopsis leaf development, however, remains elusive. We applied a poly(A)-tag sequencing (PAT-seq) technique to characterize APA-mediated regulation events in cotyledon and in five stages of true leaf development. Over 60% APA was identified in genes expressed in leaves, consistent with the results in previous publications. However, a reduced APA level was detected in younger leaves, reaching to 44% in the 18th true leaf. Importantly, we also found that >70% of the poly(A) site usages were altered in the 2nd true leaf relative to the cotyledon. Compared with cotyledon, more genes in the 2nd true leaf tended to use the distal site of 3’UTR, but this was not found in pairwise comparison among other true leaves. In addition, significant APA gene was found to be decreased in a pairwise comparison among true leaves, including differentially expressed genes. The APA genes identified herein were associated with specific biological processes, including metabolic and cellular processes, response to stimuli and hormones. These results provide a new insight into the regulation of Arabidopsis leaf development through APA.